Congenital Insensitivity to Pain with Anhidrosis in an Iranian Patient - Nasrollah Saleh-gohari (Basic and Clinical Neuroscience, 2013)
Congenital insensitivity to pain with anhidrosis is a rare disease of the nervous system which causes one to lose their feeling of pain. The disease is subtype four of hereditary sensory and autonomic neuropathy (HSAN IV) that results from NTRK1 gene defect. Direct sequencing was performed to screen NTRK1 for mutations. The result revealed a homozygous deletion of adenine on intron 14 that may cause the disease.